Optimization of Deposition Parameters for high Quality a-SiGe:H Thin Films - Mursal Mursal; Ida Usman; Toto Winata; Sukirno Sukirno; Mohamad Barmawi (Jurnal Matematika & Sains, 2006)
The effect of substrate temperature and rf power on the characteristics of a-SiGe:H alloys thin films has been investigated. The a-SiGe:H films made from a mixture of 10% silane (SiH4) and 10% germane (GeH4) gas diluted in hydrogen (H2) were grown on corning glass 7059 by using Plasma Enhanced Chemical Vapor Deposition (PECVD) method. The results showed that the deposition rate of a-SiGe:H films increased with the increasing of substrate temperature and rf power. The optical band gap (Eopt) of the films was improved by increasing of the rf power. The dependency of Eopt on the rf power is attributed to the change in Ge content in the films. The photosensitivity (Ïph/Ïd) of the films deposited at 200 Â°C and 175 Â°C slightly increased with increasing of rf power from 30-50 Watt. For the films deposited at 225 Â°C, the photosensitivity increased with increasing of rf power from 30-40 Watt, and relatively constant at rf power of 40-60 Watt.